Activation of the Nrf2/HO-1 pathway restores N-acetylcysteine-induced impairment of the hypothalamus-pituitary-adrenal axis negative feedback by up-regulating GRα expression and down-regulating GRβ expression into pituitary glands - Chaves, Amanda Silva; Ventura, Raíssa Duarte; Pacini, Maria Florencia; Magalhães, Nathalia Santos; Silva, Patrícia Machado Rodrigues e; Martins, Marco Aurélio; Pérez, Ana Rosa; Carvalho, Vinicius Frias (Frontiers in Endocrinology, 2025)
We previously showed that antioxidants induced an impairment of negative feedback of the hypothalamus-pituitary-adrenal (HPA) axis in rats, in parallel to a down-regulation of the glucocorticoid receptor (GR) and nuclear factor erythroid 2-related factor 2 (Nrf2) expression in the pituitary gland. This study evaluated the role of the Nrf2-heme-oxygenase-1 (HO-1) pathway on the impairment of the negative feedback of the HPA axis induced by N-acetylcysteine (NAC). Male Swiss-Webster mice were orally supplemented with NAC for 5 consecutive days. The Nrf2-HO-1 pathway activator cobalt protoporphyrin IX (CoPPIX) was injected intraperitoneally on days 2 and 5 after the starting of NAC supplementation. NAC reduced the expression of Nrf2 in the pituitary of mice. Furthermore, NAC induced adrenal enlargement and hypercorticoidism, along with a decrease in the GRα expression and an increase of GRβ expression in the pituitary gland. Treatment with CoPPIX reduced adrenal enlargement, systemic corticosterone levels, and GRβ expression in the pituitary gland of mice supplemented with NAC, besides increasing the expression of GRα. CoPPIX treatment also restored the failure in the negative feedback of the HPA axis induced by NAC. In conclusion, these findings showed that NAC reduced the Nrf2-HO-1 pathway activation in the pituitary gland, in a mechanism probably related to a local downregulation of GRα and an up-regulation of GRβ, leading to a failure of negative feedback of the HPA axis and consequently to the hyperactivity of this neuroendocrine axis.